2021
DOI: 10.1021/acs.jmedchem.0c02067
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of Subtype-Selective Fluorescent Antagonists for the Study of the Human Adenosine A1 Receptor in Living Cells

Abstract: The adenosine A1 receptor (A1AR) is a G-protein-coupled receptor (GPCR) that provides important therapeutic opportunities for a number of conditions including congestive heart failure, tachycardia, and neuropathic pain. The development of A1AR-selective fluorescent ligands will enhance our understanding of the subcellular mechanisms underlying A1AR pharmacology facilitating the development of more efficacious and selective therapies. Herein, we report the design, synthesis, and application of a novel series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 104 publications
0
3
0
Order By: Relevance
“… 41 , 42 BODIPY 630/650‐X was selected as the fluorophore moiety, due to its excellent optical properties and established use in the development of a toolbox of subtype‐selective fluorescent ligands for the family of the adenosine receptors. 28 , 33 , 34 A previous structure–activity relationship (SAR) study of PSB‐603 analogues indicated that para‐substitution of the terminal aromatic ring, with lipophilic substituents, is well tolerated. 43 Correspondingly, we sought to extend from this position via an aminoethyl handle which enabled us to directly attach the BODIPY 630/650‐X fluorophore (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 41 , 42 BODIPY 630/650‐X was selected as the fluorophore moiety, due to its excellent optical properties and established use in the development of a toolbox of subtype‐selective fluorescent ligands for the family of the adenosine receptors. 28 , 33 , 34 A previous structure–activity relationship (SAR) study of PSB‐603 analogues indicated that para‐substitution of the terminal aromatic ring, with lipophilic substituents, is well tolerated. 43 Correspondingly, we sought to extend from this position via an aminoethyl handle which enabled us to directly attach the BODIPY 630/650‐X fluorophore (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…96‐well white clear‐bottomed plates and 35 mm Cellview 4‐quadrant culture dishes were from Greiner bio‐one (Kremsmunster, Austria). The synthesis of the fluorescent ligands AV039 (compound 19 in 33 ), EC069 (compound 44b in 34 ) and EC005 (compound 12 in 22 ) have been described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed structure–function knowledge is typically necessary to identify ligand positions that can be harnessed for linker/fluorophore functionalization. This is particularly challenging for small ligands but has been successfully accomplished for adenosine, histamine, and ß-adrenergic , receptors. Melatonin receptors present a particularly difficult case in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, radiolabeled peptide probes have been used to investigate receptor binding and peptide-stimulated receptor internalization. , More recently, fluorescent imaging techniques have matured and are increasingly used to investigate these aspects of receptor biology. , These methods involve using either fluorescently labeled peptides or antibodies that target the receptor to allow visualization and quantification of internalization. Characterized fluorescently labeled probes are invaluable pharmacological tools that aid the understanding of agonist-mediated internalization for a wide range of receptors. Fluorescently labeled PACAP or VIP has previously been generated and used to investigate receptor internalization or tissue distribution. ,, However, several of these tools were not site-specifically labeled, as the synthesis approach used could generate a mixture of peptides labeled at different sites, or were not robustly pharmacologically characterized.…”
mentioning
confidence: 99%
“…30,31 More recently, fluorescent imaging techniques have matured and are increasingly used to investigate these aspects of receptor biology. 32,33 These methods involve using either fluorescently labeled peptides or antibodies that target the receptor to allow visualization and quantification of internalization. Characterized fluorescently labeled probes are invaluable pharmacological tools that aid the understanding of agonist-mediated internalization for a wide range of receptors.…”
mentioning
confidence: 99%